Volume support ventilation versus pressure support ventilation as a weaning mode of mechanically ventilated patients with chronic obstructive pulmonary disease - Maha K Ghanem; Hoda A Makhlouf; Alaa M Taghyan; Ali A Hassan (Egyptian Journal of Chest Disease and Tuberculosis, 2024)
Background A dual controlled ventilatory mode called volume support ventilation (VSV) is anew mode, which is intended to speed up weaning and encourage spontaneous breathing. The purpose of the study was to compare the effectiveness of pressure support ventilation (PSV) and VSV in weaning patients with chronic obstructive pulmonary disease (COPD) who are mechanically ventilated.